Acculturation of Modern Civilization for Jungle Tribes in Southeast Asia: The Case Study Kubu Tribe - Ahmad Suradi; Sukarno Sukarno; Qolbi Khoiri; Nilawati Nilawati (Journal of the Community Development in Asia (JCDA), 2021)
The Kubu tribe life is governed by the rules, norms and customs that apply in accordance with their belief. With these conditions, the problem which need to be discussed is how to acculturate modern civilization in the Kubu tribe. This research method is descriptive qualitative, the research intended to investigate the circumstances, conditions or other things that have been mentioned, the results of which are presented in the form of research reports. In this study, data were obtained from interviews with community leaders, traditional leaders, and the Kubu community. The results show that the implementation of acculturation of modern civilization in the Kubu Tribe is approaching the Kubu Tribe group, because they are still ashamed and inferior about mingling with the outside community. One strategy used by community leaders in introducing modern civilization to the Kubu tribe groups is approaching and providing counseling and model community life patterns as usual such as providing counseling in the fields of law, politic, education, religion, trading and introducing other community cultures. Unfortunately, the percentage of the allocation of funds for the empowerment of Kubu tribe is still relatively small compared to other social problems such as unemployment, homeless people and education problems.